Ectomycorrhizal community associated with Cedrus deodara in four urban forests of Nantong in East China - Wen, Zhugui; Lin, Chunyan; Xu, Xiaoming; Ma, Simiao; Peng, Yue; Sun, Yue; Tang, Boping; Shi, Liang (Frontiers in Plant Science, 2023)
Ectomycorrhizal (ECM) fungi play fundamental roles in host plant growth and terrestrial ecosystems. Cedrus deodara is cultivated in several regions in China, has high ecological, economic and medicinal value, for its afforestation and providing timber and wood oil. Here, we investigated four urban C. deodara forests in Nantong, East China, and performed bioassay experiments using soils collected from these forests. In total, we identified 19 ECM fungal species, of which 13 species were found in mature forests and 9 species were identified in bioassay experiments, with only 3 species shared. Soil pH and available P content had significant effects on species occurrence in both mature trees and bioassay seedlings on local scales. ECM communities clearly (A = 0.391, p = 0.006) separated mature forests from spore banks. Thelephoracae was the richest family we detected associated with C. deodara, while Trichophaea sp. was the most dominant in mature forests, and Wilcoxina sp. was dominant in spore banks. ECM richness affected the growth of bioassay seedlings, especially after inoculation with 2 ECM species, promoting root growth, significantly (F = 3.028, p = 0.050), but it had no effects on shoots (F = 1.778, p = 0.177). No effect of inoculation rate was found on seedlings growth. To conserve this important tree species, the ECM fungi that are associated with it should be considered.